2013
DOI: 10.7314/apjcp.2013.14.9.5409
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Pattern Recognition of Endometriomas Mimicking Ovarian Cancer

Abstract: Background: To assess the accuracy of ultrasound in differentiating endometrioma from ovarian cancer and to describe pattern recognition for atypical endometriomas mimicking ovarian cancers. Materials and Methods: Patients scheduled for elective surgery for adnexal masses were sonographically evaluated for endometrioma within 24 hours of surgery. All examinations were performed by the same experienced sonographer, who had no any information of the patients, to differentiate between endometriomas and non-endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“… 9 However, the ultrasound morphology of OE is variable, possibly due to the appearances of solid components, mural nodules, or papillary projections from a cyst wall and the degradation of internal blood products or retracted blood clots that appeared solid over time. 10 A blood clot next to the inner wall of the cyst containing the ground glass background shows an oval- or crescent-shaped lesion. 11 In general, the presence of mural nodules and papillary projections is considered to constitute evidence of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“… 9 However, the ultrasound morphology of OE is variable, possibly due to the appearances of solid components, mural nodules, or papillary projections from a cyst wall and the degradation of internal blood products or retracted blood clots that appeared solid over time. 10 A blood clot next to the inner wall of the cyst containing the ground glass background shows an oval- or crescent-shaped lesion. 11 In general, the presence of mural nodules and papillary projections is considered to constitute evidence of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The presence of mural nodule suggests malignancy, and solid masses and papillary projections in ovarian endometriomas were the most common forms mimicking ovarian cancer on sonographic morphology. 17 Therefore, sonographic appearances are generally less objective. Meanwhile, according to the International Ovarian Tumor Analysis (IOTA) studies, transvaginal ultrasound characteristics could contribute to the improvement of the management of suspicious ovarian masses.…”
mentioning
confidence: 99%
“…Finally, 134 articles were considered eligible for the systematic review; of these, 118 were also excluded for the absence of reported outcomes related to AE or the design of the study not in line with the inclusion criteria. Overall, 16 studies were finally selected for this review, 14 retrospective studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and 2 prospective studies [ 27 , 28 ]. The selection process is summarized in the PRISMA flowchart in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Three articles investigated the role of sonography in the evaluation and differential diagnosis between AE and EAOC ( Table 4 ). Subjective assessment by expert operators demonstrated higher sensitivity (89.73% vs. 64.38%) and specificity (97.15% vs. 96.54%) compared to simple rules [ 28 ].…”
Section: Resultsmentioning
confidence: 99%